Optimization of piston bowl and valve system in compression ignition engine fueled with gasoline/diesel/polyoxymethylene dimethyl ethers for high efficiency. (February 2021) - Li, Bowen; Liu, Haoye; Yu, Linjun; Wang, Zhi; Wang, Jianxin
Polyoxymethylene dimethyl ethers, with excellent volatility and oxygen content of up to 49%, have great potential to improve engine performance and emission characteristics. In this study, experiments were carried out in a single-cylinder engine fueled with gasoline/diesel/polyoxymethylene dimethyl ethers blend fuel using multiple premixed compression ignition combustion mode along with engine optimization to exploit the high-efficiency potential. The thermal efficiency was increased by 9.4 percentage points after transforming the combustion mode from conventional diesel mode to gasoline/diesel/polyoxymethylene dimethyl ethers multiple premixed compression ignition mode. A fully variable valve system and a redesigned low-heat-transfer piston were used to further improve the thermal efficiency. The low-heat-transfer piston had a 15% lower area–volume ratio compared with the original ω-type piston. By replacing the original ω-type piston with the low-heat-transfer piston, the heat transfer loss was reduced by 2.29 percentage points and thus indicated thermal efficiency could be increased by 2.37 percentage points, which was up to 50.03%. On the basis of the low-heat-transfer piston, indicated thermal efficiency could be further increased to 51.09% with the application of fully variable valve system due to the longer ignition delay and more premixed combustion. At the same time, NOX emissions could be controlled below 0.4 g/kW·h using high exhaust gas recirculation ratio, which equaled the NOX emission limit of Euro VI standard. Although soot emissions could be increased due to weak turbulence and insufficient intake charge using the low-heat-transfer piston and fully variable valve system, it was still lower than those of the original diesel engines.